2011
DOI: 10.1038/ajg.2010.512
|View full text |Cite
|
Sign up to set email alerts
|

Small Bowel Homing T Cells Are Associated With Symptoms and Delayed Gastric Emptying in Functional Dyspepsia

Abstract: Cellular immune activation with increased small bowel homing T cells may be key factors in the clinical manifestations of H. pylori-negative FD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
156
2
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 167 publications
(184 citation statements)
references
References 56 publications
10
156
2
16
Order By: Relevance
“…There is also evidence of aberrant immune activation in the peripheral blood of patients with FD. The levels of gut-homing T cells are increased, and cultured peripheral blood immune cells produce excess inflammatory cytokines that are linked to delayed gastric emptying [108]. This work suggests that a proportion of FD is an immune-mediated disease driven by allergic type T h 2 inflammation.…”
Section: Immunological Disorders In Fdmentioning
confidence: 87%
“…There is also evidence of aberrant immune activation in the peripheral blood of patients with FD. The levels of gut-homing T cells are increased, and cultured peripheral blood immune cells produce excess inflammatory cytokines that are linked to delayed gastric emptying [108]. This work suggests that a proportion of FD is an immune-mediated disease driven by allergic type T h 2 inflammation.…”
Section: Immunological Disorders In Fdmentioning
confidence: 87%
“…1) were increased in patients with functional dyspepsia and correlated with symptom intensity and impaired gastric emptying, suggesting that gastric disturbances in functional dyspepsia could, in fact, be secondary to duodenal inflammation 94 . Together with data of increased duodenal eosinophilia 90,91,95,96 , these studies have demonstrated that low-grade mucosal inflammation plays a key part in the pathogenesis of functional dyspepsia.…”
Section: Gastroduodenal Inflammationmentioning
confidence: 95%
“…T H 2 cells also express IL-4 and IL-13, which provide feedback to the stomach and can promote immunoglobulin (Ig) class-switching in B cells and induce the expression of pro-allergic IgE antibodies, which further stimulate eosinophil degranulation and increase epithelial permeability. The pro-inflammatory cytokines tumour necrosis factor (TNF) and IL-1β and the anti-inflammatory cytokine IL-10 can be released by immune cells into the blood and promote, along with small-intestinal-homing T cells (expressing T cell surface glycoprotein CD4, integrin β7 (α4β7) and CC-chemokine receptor type 9 (CCR9)), an anxiety or stress response, which in turn can lead to disordered motility and visceral hypersensitivity in the stomach and duodenum 37,94 .…”
Section: Gastroduodenal Sensitivitymentioning
confidence: 99%
“…Classifi cation of patients according to the IBS subtype is rarely performed, but when this is done clear diff erences in immune profi le are observed with increased concentrations of T H 1-type cytokines, including TNF-α and IL-1 β , detected alongside typical T H 2 cytokines, such as IL-10, in IBS-D ( 85,87,88 ). Th e lack of polarization toward a T H 1 or T H 2 axis indicates the nature of immune activation in IBS is not straightforward but instead likely to be a complex pheno menon incorporating several distinct cell types and / or possibly cells with plasticity of function ( 97 ).…”
Section: -Htmentioning
confidence: 99%